2019
DOI: 10.1186/s12943-019-1062-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the dynamic tumor microenvironment in controversies regarding immune checkpoint inhibitors for the treatment of non-small cell lung cancer (NSCLC) with EGFR mutations

Abstract: Immunotherapy has been incorporated into the first- and second-line treatment strategies for non-small cell lung cancer (NSCLC), profoundly ushering in a new treatment landscape. However, both adaptive signaling and oncogenic (epidermal growth factor receptor (EGFR)-driven) signaling may induce PD-L1 upregulation in NSCLC. Nevertheless, the superiority of immune checkpoint inhibitors (ICIs) in advanced EGFR-mutant NSCLC is only moderate. ICIs appear to be well tolerated, but clinical activity for some advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
147
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 202 publications
(266 reference statements)
1
147
1
Order By: Relevance
“…The largest coe cient of the number of the driver gene in the multivariable LR model also illustrates its absolute importance in developing non-patient-matched genotypes. Secondly, PDX models from EGFR mutant lung cancers were reported with poor histological differentiation, and frequent loss of EGFR mutations [34], which supported the high inconsistent risk of EGFR mutant NOG/PDX models in this study. Thirdly, the evidence that pemetrexed increased the number of TILs, and upregulated immune-related genes related to antigen presentation might support the conclusion that PDX models from patients receiving pemetrexed are less likely to maintain the original genotypes [35].…”
Section: Discussionsupporting
confidence: 82%
“…The largest coe cient of the number of the driver gene in the multivariable LR model also illustrates its absolute importance in developing non-patient-matched genotypes. Secondly, PDX models from EGFR mutant lung cancers were reported with poor histological differentiation, and frequent loss of EGFR mutations [34], which supported the high inconsistent risk of EGFR mutant NOG/PDX models in this study. Thirdly, the evidence that pemetrexed increased the number of TILs, and upregulated immune-related genes related to antigen presentation might support the conclusion that PDX models from patients receiving pemetrexed are less likely to maintain the original genotypes [35].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, this study included 73% of patients with PD-L1 ≥ 50%, thus illustrating the poor response in EGFR-mutated NSCLC even with high PD-L1 expression [3]. Several reasons to these poor outcomes have been identi ed, such as the association of EGFR mutation with low tumor mutation burden (TMB) and the lack of T cell in ltration while PD-L1 expression is variable [2,13,14]. Nevertheless, some studies showed that patients with uncommon EGFR (including G719X, L861Q, S768I, and Ex20 ins) mutations have a good immunotherapy potential [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines do not recommend immunotherapy to patients with NSCLC harboring EGFR mutation at present [7][8]. Several mechanisms for poor responses to ICIs have been reported, such as a lower TMB and an unin amed and immunosuppressive TME [9][10][11][12][13][14][15][16]. PD-1/PD-L1 axis may not be the main immune escape route in EGFR mutant lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have con rmed that EGFR mutations in NSCLC are closely related to an immunosuppressive tumor microenvironment (TME) [9][10][11][12][13] and a lower tumor mutation burden (TMB) [10,[14][15], which cause an inferior response to PD-1 blockade in NSCLCs. EGFR mutations can lead to an unin amed and immunosuppressive TME, with immunological tolerance, and weak immunogenicity [10,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation